Lecturer Research Management Information System Iakn Manado - Willy Armando Rondonuwu; Olivia Cherly Wuwung; Jhoni Lagun Siang (International Journal of Education, Information Technology, and Others, 2025)
The management of lecturers’ research at the State Christian Institute of Manado (IAKN Manado) was previously conducted manually, resulting in administrative delays and difficulties in monitoring. Furthermore, the existing system lacked integration and did not support real-time collaboration among lecturers, administrators, and reviewers. This study aims to develop a Lecturer Research Management Information System application designed to simplify, accelerate, and improve the accuracy of research management, while integrating the values of High Touch and High Tech in its implementation. The development method employed was Extreme Programming (XP), comprising the stages of planning, design, coding, and testing. The resulting application features proposal uploads, document validation, automated notifications, progress monitoring, and real-time report generation. The integration of High Touch and High Tech values ensures that the system is not only technologically functional but also promotes relationships, academic ethics, and Christian values. Testing results indicate that the application meets user requirements and is ready for implementation at IAKN Manado. Future development recommendations include integration with national publication databases (SINTA and Garuda), mobile application development, enhanced data security through layered encryption and two-factor authentication, as well as user training to maximize system utilization.